(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
One of the most important aspects of any business model is how it enables the company toachieve its financial goals. Defining a company’s place in the value chain is a key part of a business plan.E-business model refers to a business model that employs electronic communication technologies like theinternet to exchange information. In the e-business model, a firm’s customers, allies, and suppliers theprimary flows of goods, services, information and money and the major advantages to participants are allincluded. This paper contains review on models of e-business, mobile business mobile banking.